Cover Image, Volume 120, Number 2, August 1, 2019. Issue 2 (16th July 2019) - Petrovic, Ivana; Ahmed, Zain U.; Hay, Ashley; Rosen, Evan B.; Lu, Chuanyong; Hameed, Meera; Shah, Jatin P.
Abstract : The cover image is based on the Research Article Sarcomas of the mandible by Ivana Petrovic et al., 10.1002/jso.25477 .